LEGAL ASPECTS OF JUSTICE IN CRIMINAL LAW ENFORCEMENT - Carolina da Cruz (Jurnal Pembaharuan Hukum, 2019)
Criminal Law enforcement is an effort to realize legal ideas and concepts oriented to legal certainty as a noble ideal that must be applied by the state. The implementation of justice in criminal law enforcement in Indonesia can be said to be far from the goals to be realized by the rule of law. Enforcement of law and justice in the context of a fair legal process is a guarantee of the rule of law based on the constitution that must be able to realize and be felt by the people seeking justice as a reality. The law that is implemented and enforced must be a law that contains the values of justice, therefore, the true nature of law enforcement lies in the activity of harmonizing the relationships of values that are interpreted in the rules that are stable and manifest and act as a series of translation of the stage value the end, to create, preserve, and maintain the peace of association of life. In essence, the establishment of law and justice is a form of human welfare physically and mentally, socially, and morally.